Gelatinase B/matrix metalloproteinase-9 and other neutrophil proteases switch off interleukin-2 activity. Issue 15 (9th August 2019) - Rybakin, Vasily; Stas, Melissa; Ugarte-Berzal, Estefania; Noppen, Sam; Vandooren, Jennifer; Van Aelst, Ilse; Liekens, Sandra; Proost, Paul; Opdenakker, Ghislain
Abstract : Interleukin 2 (IL-2) is critical for T cell development and homeostasis, being a key regulator of adaptive immune responses in autoimmunity, hypersensitivity reactions and cancer. Therefore, its abundance in serum and peripheral tissues needs tight control. Here, we described a new mechanism contributing to the immunobiology of IL-2. We demonstrated, both in biochemical and cell-based assays, that IL-2 is subject to proteolytic processing by neutrophil matrix metalloproteinase-9 (MMP-9). IL-2 fragments produced after cleavage by MMP-9 remained linked by a disulfide bond and displayed a reduced affinity for all IL-2 receptor subunits and a distinct pattern and timing of signal transduction. Stimulation of IL-2-dependent cells, including murine CTLL-2 and primary human regulatory T cells, with cleaved IL-2 resulted in significantly decreased proliferation. The concerted action of neutrophil proteases destroyed IL-2. Our data suggest that in neutrophil-rich inflammatory conditions in vivo, neutrophil MMP-9 may reduce the abundance of signaling-competent IL-2 and generate a fragment that competes with IL-2 for receptor binding, whereas the combined activity of granulocyte proteases has the potential to degrade and thus eliminate bioavailable IL-2.